Theoretical modeling and experimental verification of circular Halbach electromagnetic energy harvesters for performance enhancement. (10th August 2018) - Zhang, Ying; Cao, Junyi; Liao, Wei-Hsin; Zhao, Libo; Lin, Jing
Abstract: Circular Halbach magnetic arrays are employed to improve the performance of electromagnetic energy harvesters (EMEH). However, it is difficult to predict and enhance the performance of EMEH due to the facts that there are few theoretical models of circular Halbach EMEHs for accurately characterizing the magnetic field strength and voltages. Motivated by the demand of the optimization for magnetic field strength and system parameters, the theoretical model of the circular Halbach EMEHs is developed to predict the magnetic flux density and voltage. Numerical simulations of the magnetic flux density with different system parameters are performed to demonstrate that the proposed model can well predict the magnetic flux density. To verify the theoretical model and investigate the influence of system parameters on the output voltage, the electromagnetic energy harvesting experiments for extracting energy from bearing rotational motion are established with adjustable geometric parameters and phase differences. Experimental results under different conditions indicate that the theoretical model can be applied to estimate the output voltage of the EMEH. Furthermore, these parameters including gap distance between magnets and coils, rotational speed and coil radius are analyzed to enhance the performance of EMEH under rotational motion specializing the bearing condition monitoring.